2004
DOI: 10.1152/ajpcell.00142.2003
|View full text |Cite
|
Sign up to set email alerts
|

PI3K induced actin filament remodeling through Akt and p70S6K1: implication of essential role in cell migration

Abstract: This study was designed to identify the molecular mechanisms of phosphatidylinositol 3-kinase (PI3K)-induced actin filament remodeling and cell migration. Expression of active forms of PI3K, v-P3k or Myr-P3k, was sufficient to induce actin filament remodeling to lead to an increase in cell migration, as well as the activation of Akt in chicken embryo fibroblast (CEF) cells. Either the inhibition of PI3K activity using a PI3K-specific inhibitor, LY-294002, or the disruption of Akt activity restored the integrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
137
2
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 175 publications
(152 citation statements)
references
References 37 publications
12
137
2
1
Order By: Relevance
“…In our previous studies, we showed that p70S6K1-KD inhibited endogenous p70S6K1 activities in CEF cells (Qian et al, 2004). Here, we show that overexpression of p70S6K1-KD partially inhibited ILK-induced cell migration and invasion (Figure 4e), indicating that p70S6K1 is involved in ILK-induced cell mobility.…”
Section: Disruption Of Either Akt or P70s6k1 Inhibits Ilk's Ability Bsupporting
confidence: 67%
“…In our previous studies, we showed that p70S6K1-KD inhibited endogenous p70S6K1 activities in CEF cells (Qian et al, 2004). Here, we show that overexpression of p70S6K1-KD partially inhibited ILK-induced cell migration and invasion (Figure 4e), indicating that p70S6K1 is involved in ILK-induced cell mobility.…”
Section: Disruption Of Either Akt or P70s6k1 Inhibits Ilk's Ability Bsupporting
confidence: 67%
“…Oncogenic transformation by Ras and c-Myc is traditionally associated with alterations in the cytoskeletal architecture and overall cell morphology (Qian et al, 2004;Kharitonova et al, 2007). Phalloidin staining was performed to examine F-actin structures in Rb-proficient and -deficient cells (Figure 1d).…”
Section: Rb Loss Cooperates With Discrete Oncogenes Jl Dean Et Almentioning
confidence: 99%
“…Recent reports have shown that PI3K induces actin filament remodeling through Akt and p70 S6K (15,16). When AGS cells were treated with 40 ng/mL rhTP or 40 Amol/L D-dRib, the level of phosphorylated Akt increased as early as 6 hours after treatment.…”
Section: Tp-related Invasion Activity Is Dependent On the Phosphatidymentioning
confidence: 90%